2010
DOI: 10.1007/s12032-010-9625-x
|View full text |Cite
|
Sign up to set email alerts
|

Safe use of sorafenib in a patient undergoing salvage liver transplantation for recurrent hepatocellular carcinoma after hepatic resection

Abstract: Sorafenib, a multikinase inhibitor targeting angiogenesis, cell survival, and proliferation in hepatocellular carcinoma (HCC) is a standard therapy for advanced stage disease. However, its utilization as neoadjuvant therapy is under investigation and remains an off label indication. The use of sorafenib in pre-liver transplant setting raises caveats associated with risk of bleeding, wound healing deficiencies, and hepatic decompensation. Herein, we report the case of a patient who after exhibiting HCC relapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…However, the overall experience with Sorafenib in HCC patients awaiting LT is actually even bleaker. Concerns regarding the potential negative side effects of Sorafenib have been raised [ 17 , 18 , 38 - 40 ]. Nevertheless, the performance of the trial was encouraged by emerging reports about a near absence of liver toxicity or treatment-related deaths [ 12 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall experience with Sorafenib in HCC patients awaiting LT is actually even bleaker. Concerns regarding the potential negative side effects of Sorafenib have been raised [ 17 , 18 , 38 - 40 ]. Nevertheless, the performance of the trial was encouraged by emerging reports about a near absence of liver toxicity or treatment-related deaths [ 12 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort of liver transplant recipients side effects prevented full dosing of sorafenib and necessitated discontinuation of sorafenib in the majority of patients, yet antitumor efficacy seemed promising in combination with mTORi. are yet only anecdotal [13][14][15][16][17][18]. Enhanced anticancer properties in vitro and in vivo were suggested when sorafenib was combined with mTORi [16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The use of potent VEGF inhibitors are not without concern due to their effect on angiogenesis and wound healing 42, 43. Limited experiences with preoperative use of Sorafenib in renal cell carcinomas have been published 44, while the literature in surgical HCC candidates is limited 45. Clinical trials in surgical HCC patients have been suggested 46.…”
Section: Discussionmentioning
confidence: 99%